Comparison of recurrence patterns between patients with thoracic esophageal squamous cell carcinoma treated with neoadjuvant chemoradiotherapy and postoperative adjuvant chemoradiotherapy - Ni, Kunhan; Huang, Yixuan; Lu, Simiao; Jiang, Longlin; Zhang, Huan; He, Wenwu; Wang, Chenghao; Zhou, Qiang; Li, Haojun; Li, Jialong; Wang, Kangning; Liu, Guangyuan; et al. (Frontiers in Oncology, 2025)
PurposeTo compare the recurrence patterns and survival outcomes between patients with esophageal squamous cell carcinoma (ESCC) treated with neoadjuvant chemoradiotherapy (NCRT) and adjuvant chemoradiotherapy (ACRT).MethodsWe retrospectively analyzed 267 patients with locally advanced ESCC who received treatment at Sichuan Cancer Hospital and Institute (Chengdu, China) between January 2018 and December 2020. Based on different treatment protocols, the patients were divided into two groups: NCRT (n=181) and ACRT (n=86). After propensity score matching, each group included 74 patients. This study compared the recurrence types, sites, frequencies, and timing, as well as overall survival (OS), disease-free survival (DFS), and prognostic risk factors between the two groups.ResultsThe recurrence rates in the NCRT and ACRT groups were 59.5% (44/74) and 33.8% (25/74), respectively; the difference was statistically significant (P=0.002). Recurrences primarily occurred within 2 years following esophagectomy. The ACRT group had a higher 3-year OS rate than the NCRT group (67.8% versus [vs.] 50.6%, respectively; P=0.019). In the subgroup of patients with local recurrence, the 3-year OS rate was higher in the NCRT group compared to the ACRT group (53.8% vs. 0%, respectively; P=0.029). In terms of DFS, the ACRT group exhibited better results than the NCRT group (P<0.001). Multivariate analysis revealed that pathological N staging was an independent risk factor affecting the OS prognosis of patients in the NCRT group. Margin status and pathological T staging were identified as independent risk factors influencing OS in the ACRT group, while sex and treatment regimen were independent risk factors affecting DFS in patients with postoperative pathological lymph node positivity.ConclusionThere was significant difference in the OS and DFS prognosis of patients with ESCC treated with NCRT and ACRT. Recurrence primarily occurs within 2 years following esophagectomy. The recurrence rate was higher in the NCRT group compared to the ACRT group. Patients with early recurrence had a poorer survival prognosis compared to those with late recurrence. Pathological N staging was identified as an independent risk factor affecting OS in the NCRT group. Furthermore, margin status and pathological T staging were independent risk factors influencing OS in the ACRT group.